Experiences of Sexual Assault and Financial Stability: Sense of Control as a Potential Mechanism - Furlong, Courtney (Violence against women, 2024)
This investigation utilized the Midlife in the United States Survey (N = 3,258) to assess the relationships between sexual assault, sense of control, and financial stability. Age of first sexual assault and sexual assault revictimization were also considered in analyses of sexual assault survivors’ data. Results revealed consistent associations between experiences of sexual assault and revictimization with lower financial stability and suggest that sense of control may be an indirect mechanism linking these variables. Findings have policy relevance and practical implications for practitioners. Restoring sexual assault victims’ internal loci of control may promote more positive financial outcomes.